Staatliche Organisationen und Krisenmanagement: Sonderband Leviathan - Bode, Ingo; Jungmann, Robert; Serrano Velarde, Kathia (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Crises signal eventful deviations from the normal state of affairs and prompt societies to reflect (on themselves). The Covid-19 crisis provided a stark illustration of this. In view of the apparent omnipresence of crises, the question arises as to how states have dealt with and can deal with crises in the 21st century. This special volume explores this question, focusing on organisations of the state and state-mediated organising in terms of relations between public authorities and formally state-independent organisational contexts. The book presents studies on different areas of public services and different kinds of crises from a comparative perspective. It asks how, in crisis contexts, existing expectations or tensions in this regard are dealt with in an organisational or (re)organising way, or where this fails.